Acute scrotum due to heterotopic gastric mucosa in Tunica vaginalis - Zafar Nazir; Muhammad Arif Mateen Khan; Javaria Qamar (Elsevier, 2018)
In adult and pediatric literature, most cases of heterotopic gastric mucosa are reported in gastrointestinal tract. Presences of gastric mucosa in genitourinary tract is unusual. We review the literature and report a case of 10-year old boy who presented with acute scrotum due to ulceration and bleeding from heterotopic gastric mucosa located in Tunica vaginalis. Excision of ectopic mucosa and Patent Processus vaginalis (PPV) was curative. Keywords: Acute scrotum, Heterotopic gastric mucosa, Tunica vaginalis, Inguinal hernia, Children